Development, Social Change and Environmental Sustainability Proceedings of the International Conference on Contemporary Sociology and Educational Transformation (ICCSET 2020), Malang, Indonesia, 23 September 2020 - Sumarmi, Nanda Harda Pratama Meiji; Purwasih, Joan Hesti Gita; Kodir, Abdul; Andriesse, Edo; Dorina Camelia, Ilies; Miichi, Ken (Taylor & Francis, 2021)
Nowadays, the concept of SDGs (Sustainable Development Goals) is starting to replace the concept of MDGs (Millennium Developmental Goals). It is a global goal adopted by all United Nations member states. It emphasizes the idea that the development of every country can only be achieved by balancing other factors such as social, economic, and environmental sustainability. It is already clear how sustainable development works with environmental ethics and management. However, there are still issues regarding the sustainable development and human well-being. Sustainable development should focus on finding a way for society to meet their present needs for the long term without sacrificing the ability of future generations to meet their needs. This international seminar provides research results and literature regarding the topic of sustainable development concept, the dynamics of sustainable development and social change, and environmental sustainability. The international seminar, entitled 1st International Conference on Contemporary Sociology and Educational Transformation, listed speakers from several countries providing an overview on human and environmental resilience. This book contains a selection of papers presented at the conference.